Room for discretion?: biased decision-making in international financial institutions - Lang, Valentin; Presbitero, Andrea (Journal of development economics, 2018)
We exploit the degree of discretion embedded in the World Bank-IMF Debt Sustainability Framework (DSF) to understand the decision-making process of international financial institutions. The unique, internal dataset we use covers the universe of debt sustainability analyses conducted between December 2006 and January 2015 for low-income countries. These data allow us to identify cases where the risk rating implied by the application of the DSF's mechanical rules was overridden to assign a different official rating. Our results show that both political interests and bureaucratic incentives influence the decision to intervene in the mechanical decision-making process. Countries that are politically aligned with the institutions' major shareholders are more likely to receive an improved rating; especially in election years and when the mechanical assessment is not clear-cut. These results suggest that the room for discretion international financial institutions have can be a channel for informal governance and a source of biased decision-making.
Online 14 September 2017
Gesehen am 30.10.2019